Perancangan Tempat Tidur Tingkat Lipat pada Ruang Akomodasi ABK Kapal Feri Ro-Ro 1100 GT - Sarah Salsabillah Fiddin; I Putu Sindhu Asmara; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
PT. Adiluhung Saranasegara Indonesia (PT. ASSI) is one of the shipping industries engaged in ship building and maintenance services. This year, PT. ASSI is working on one of the newshipbuilding projects, the 1100 GT ro-ro ferry called KMP. Aceh Hebat 2. This ship has 2 crew accommodation rooms on passenger deck 1 where each room has a limited area and is occupied by 4 crew members. Therefore, PT. ASSI needs furniture that can optimize the space area for the next ship project, with the realization of an innovation in the design of a folding bunk bed. This study uses the Ulrich design method with the output of 3 design concepts, then one selected design is determined in terms of functionality, strength, and operations. Design and analysis of structural strength using Autodesk Fusion 360 software. Design concept 1 was chosen because when it is folded it produces a free area of 4.37 m2, and provides a table for crew needs to work on reports. Analysis of the overall structural strength on the selected design concept obtained a minimum safety factor value is 1.81 onthe lower frame deck, the maximum safety factor value is 15 on the top frame deck, the maximum von Mises stress value is 137.2 MPa on the lower frame deck, and the minimum von mises stress value is 1,951 x 10-4 MPa on the top frame deck. The total budget required for its manufacture is Rp.6.225,402,-.